O dispositivo do tempo e a constituição do sujeito pesquisador - Walter, Bruno Eduardo Procopiuk (2014)
Inspired by Michel Foucault, especially in his contributions on the power relations and ethics of self-care, this research aimed to answer the following problem: how is the researcher subject constituted , in the State University of Maringá, from the device of time? The author of this work used the genealogical methodol present in Nietzsche and retaken by the French philosopher to understand the power relations through which the researcher is produced. It is important to remember that the genealogy does not presuppose immutable essences which are given a priori, because, for it, the subject is understood as the effect of a given state forces. Thus, we sought to understand the conditions and circumstances in which the researcher subject was born, developed and changed, or, in other words, we sought his empirical birth. In order to understand the formation of the researcher subject, the category of device had fundamental importance, since it served as methodological operator aiding in the analysis of discursive practices, power practices and subjectivity process. Among the various devices involved in the constitution of the researcher subject, we chose to focus on the device of time. This one was proposed as a theoretical hypothesis by the author of this work and aimed to give visibility to the field of forces in which the researcher is engendered. The analysis of this device used several and heterogeneous elements, such as public notices, regulations, laws, websites, among others. Nine interviews were also conducted and other twenty-one (made by Gois, 2012, 2013) were consulted. From the analysis it was possible to draw a cartography of the production lines of the researcher's subjectivity, perceiving through school-university the kidnapping of his existence. It was noted a must for the time of the researcher to be increasingly used in an extensive and productive way. A number of factors such as reward research productivity (given by of the Conselho Nacional de Desenvolvimento Científico e Tecnológico), the lattes curriculum, assessments of post-graduate (made by the Coordenação de Pessoal de Ensino Superior), among others contributed for this. If on one hand the device of time acts on researchers by giving them certain contours, on the other had resistance emerges in opposition - especially expressed through the exercise of reflection as a practice of freedom. Thus, in conclusion, it was emphasized that the researcher form finds a special place to be in the University. There are, however, researcher subjects who are escaping the forms of subjectivity experienced by the device of time that are outside this frame that constitutes the researcher in the universities. It is noteworthy, therefore, the need for other forms of existence and subjectivity that transpose the device of time.